Ancient Rome and the construction of modern homosexual identities - Ingleheart, Jennifer (Classical presences, 2015)
"Much has been written about the contribution of ancient Greece to modern discourses of homosexuality, but Rome's significant role has been largely overlooked. Ancient Rome and the Construction of Modern Homosexual Identities explores the contested history of responses to Roman antiquity, covering areas such as literature, the visual arts, popular culture, scholarship, and pornography. Essays by scholars working across a number of disciplines analyse the demonization of Rome and attempts to write it out of the history of homosexuality by early activists such as John Addington Symonds, who believed that Rome had corrupted ideal (and idealized) 'Greek love' through its decadence and sexual licentiousness. The volume's contributors also investigate the identification with Rome by men and women who have sought an alternative ancestry for their desires. The volume asks what it means to look to Rome instead of Greece, theorizes the way in which Rome itself appropriates Greece, and explores the consequences of such appropriations and identifications, both ancient and modern.From learned discussions of lesbian cunnilingus in Renaissance commentaries on Martial and Juvenal, to disgust at the sexual excesses of the emperors, to the use of Rome by the early sexologists, to modern pornographic films that linger on the bodies of gladiators and slaves, Rome has been central to homosexual desires and experiences. By interrogating the desires that create engagements with the classical past, the volume illuminates both classical reception and the history of sexuality"--Jacket cover.